Orbital cellulitis: early intervention saves vision - Rajeshwari, N.; Savitha, A. (International Journal of Contemporary Pediatrics, 2019)
Orbital cellulitis describes an infection involving the soft tissues posterior to the orbital septum including the fat and muscle within the bony orbit. This condition is associated with severe sight and life-threatening complications. Distinguishing it from preseptal cellulitis is difficult, but important. Acute sinusitis is the commonest predisposing factor. Clinical findings alone are not specific enough to distinguish between preseptal and post septal orbital cellulitis. Early diagnosis using CT orbit is important to rule out complications such as orbital cellulitis, subperiosteal abscess. The most common location of subperiosteal abscess is the medial wall of the orbit. Transnasal endoscopic drainage of the abscess is a functional and minimally invasive technique and is the treatment of choice at present. Early diagnosis and intervention are mandatory to prevent the visual loss and life-threatening complication. Here, the authors describe a 2 months old infant with orbital cellulitis and medial subperiosteal abscess and treated with transnasal endoscopic drainage of the subperiosteal abscess.